2018
DOI: 10.1186/s41100-018-0181-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pleuroperitoneal leak caused by diaphragm blebs in a peritoneal dialysis patient: a case report with literature review

Abstract: Background: Pleuroperitoneal leak is an uncommon but significant complication of peritoneal dialysis. Although the exact pathogenesis of pleuroperitoneal communication remains unclear, the pressure gradient between the thorax and abdominal cavity has been thought to play a major role. Case presentation: A 48-year-old man with diabetes mellitus and hypertension who had been treated with continuous ambulatory peritoneal dialysis (1.5 L dwells four times a day) for 3 months was admitted because of massive right-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
(23 reference statements)
0
6
0
2
Order By: Relevance
“…Hydrothorax is postulated to be associated with a PPF that is formed secondary to a congenital diaphragmatic defect or an acquired defect, resulting in the movement of dialysate from the peritoneum to the pleural cavity [1,2]. Alteration in the pleuroperitoneal pressure gradient secondary to PD that occurred over a 21-month period in our patient may have triggered PPF [5].…”
Section: Discussion/conclusionmentioning
confidence: 73%
See 1 more Smart Citation
“…Hydrothorax is postulated to be associated with a PPF that is formed secondary to a congenital diaphragmatic defect or an acquired defect, resulting in the movement of dialysate from the peritoneum to the pleural cavity [1,2]. Alteration in the pleuroperitoneal pressure gradient secondary to PD that occurred over a 21-month period in our patient may have triggered PPF [5].…”
Section: Discussion/conclusionmentioning
confidence: 73%
“…CT peritoneography is advantageous for depicting the entire peritoneal and thoracic cavity with minimal costs compared with magnetic resonance peritoneography [6]. Peritoneal scintigraphy may be performed using technetium-99m macroaggregated albumin ( 99m Tc-MAA) as the contrast agent [5]. We used iohexol as the contrast agent, which highlights a characteristic imaging feature of PPF.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The mechanism underlying the development of ascites in the pleural effusion is considered to be related to the increased intra-abdominal pressure due to the accumulation of PD dialysate or liver cirrhosis in the presence of a diaphragmatic defect, such as those around the major vessels and the esophagus or through the diaphragmatic foramina or lymphatics [1,2]. Previous studies have reported that once blebs that form on fragile regions in the diaphragm due to intra-abdominal pressure are ruptured, they could cause a hydrothorax and a one-way valve [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Se ha postulado que el hidrotórax se asocia con una FPP que se forma como consecuencia de un defecto congénito del diafragma o un defecto adquirido, lo que genera el movimiento del dializado del peritoneo a la cavidad pleural [1, 2]. Una alteración en el gradiente de presión pleuroperitoneal secundaria a la DP que ocurrió durante un periodo de 21 meses pudo haber disparado la FPP en nuestro paciente [5].…”
Section: Discusión/conclusiónunclassified
“…La peritoneografía mediante TC es ventajosa para retratar la cavidad peritoneal y torácica completa, con costos mínimos en comparación con la peritoneografía mediante resonancia magnética [6]. La gammagrafía peritoneal puede realizarse utilizando albúmina macroagregada con tecnecio-99 como agente de contraste [5]. En este caso empleamos iohexol como agente de contraste, que realza el rasgo de imagen característico de la FPP.…”
Section: Discusión/conclusiónunclassified